2001
DOI: 10.1016/s0893-133x(00)00175-5
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of 5-HT1A Autoreceptors by a Low Chronic Fluoxetine Dose Effect of the Concurrent Administration of WAY-100635

Abstract: Using microdialysis, receptor autoradiography and in situ hybridization, we examined the effects of fluoxetine alone or with WAY-100635 on: (a) extracellular 5-HT in frontal cortex; and (b) density and sensitivity of 5-HT 1A autoreceptors in rat brain. WAY-100635 (0.3 mg/kg, s.c.) doubled the increase in extracellular 5-HT produced by fluoxetine (3 mg/kg, i.p.) (SSRI) Selective serotonin (5-hydroxytryptamine, 5-HT) reuptake inhibitors (SSRIs) are extensively used in the treatment of major depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 55 publications
(71 reference statements)
9
76
0
2
Order By: Relevance
“…Previous works with SSRIs were not able to determine the nature of 5-HT 1A receptor alteration that occurs with chronic treatment. Indeed, whereas one study has reported a decrease in [ 3 H]-8-OH-DPAT binding in the DR after chronic fluoxetine treatment without corresponding changes in hippocampus (Welner et al, 1989), other studies have reported no changes in 5-HT 1A binding in DR, hippocampus, or cortex following chronic treatment with either fluoxetine or citalopram (Hensler et al, 1991;Hervas et al, 2001;Jolas et al, 1994;Le Poul et al, 1995). Recent observations of rapid internalization of 5-HT 1A receptors after acute administration of fluoxetine led to new questions regarding the nature of the altered processing of 5-HT 1A receptors that occurs during chronic SSRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works with SSRIs were not able to determine the nature of 5-HT 1A receptor alteration that occurs with chronic treatment. Indeed, whereas one study has reported a decrease in [ 3 H]-8-OH-DPAT binding in the DR after chronic fluoxetine treatment without corresponding changes in hippocampus (Welner et al, 1989), other studies have reported no changes in 5-HT 1A binding in DR, hippocampus, or cortex following chronic treatment with either fluoxetine or citalopram (Hensler et al, 1991;Hervas et al, 2001;Jolas et al, 1994;Le Poul et al, 1995). Recent observations of rapid internalization of 5-HT 1A receptors after acute administration of fluoxetine led to new questions regarding the nature of the altered processing of 5-HT 1A receptors that occurs during chronic SSRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After 21 days administration, there is a significant increase in SI at 7.5 mg/kg indicating that, if neurogenesis is playing a role in the anxiolytic behavior, 5-HT 1A receptor activation may have occurred at this time point, and a longer period of 5-HT elevation is required to overcome the SB-649915-B-mediated competitive 5-HT 1A receptor block. It could be suggested that chronic blockade of postsynaptic 5-HT 1A receptors will induce an increase in receptor population or sensitization, however, the literature dose not support a change in 5-HT 1A receptor sensitivity Hervas et al, 2001). The Duxon et al (2000) data showing an accelerated onset of effect following coadministration of paroxetine (3.0 mg/kg) and WAY100635 (0.1 mg/kg) clearly indicate that 5-HT 1A receptor antagonism does not have a negative impact on the SI responses.…”
Section: Discussionmentioning
confidence: 99%
“…8-OH-DPAT and WAY 100635 were injected s.c. dissolved in saline. An additional experiment in which we examined the effects of the sustained administration of fluoxetine (3 mg/kg day, dissolved in 50% DMSO) and VN2222 (6 mg/kg day, dissolved in DMSO) was carried out in which these drugs were administered with minipumps following described procedures (Hervás et al, 2001). Control rats were treated with vehicle.…”
Section: -Htmentioning
confidence: 99%
“…The increase in the synaptic concentration of 5-HT that follows reuptake inhibition is limited by a negative feedback involving 5-HT 1A autoreceptors (Adell and Artigas, 1991;Artigas et al, 1996). Following repeated treatment, 5-HT 1A receptors desensitize (Blier and de Montigny, 1994;Invernizzi et al, 1994;Hervás et al, 2001). This effect results in a reduced efficacy of the negative feedback and therefore in an increase of the extracellular concentration of 5-HT (5-HT ext ) in the forebrain (Bel and Artigas, 1993;Invernizzi et al, 1994;Rutter et al, 1994;Kreiss and Lucki, 1995).…”
Section: Introductionmentioning
confidence: 99%